Walking Towards Wellness: Exploring Community Views on Urban Walkability for a Healthier Lifestyle in Semarang - Kirana Prasetya Azizah; Bagus H. Setiadji; Haryono S. Huboyo (Jurnal Kesehatan Masyarakat, 2025)
Promoting active mobility, such as walking, is a key measure in creating a healthier urban environment. In support of Semarang City’s Urban Mobility Plan, which prioritises low-carbon strategies, the local government has undertaken extensive development of pedestrian infrastructure since 2017. This study investigates public willingness to utilise pedestrian pathways, a critical component in ensuring the effectiveness of such interventions. Data were collected through a survey involving 254 respondents across 24 major roads in Semarang. Findings indicate that walking is predominantly undertaken for shopping and health-related activities, typically covering distances between 200 and 800 metres on weekends. Destinations most frequented include shops, markets, stalls, and shopping centres. The results highlight the importance of integrating user-centred design into pedestrian infrastructure and emphasize the function of pedestrian paths as a social interaction space for both physical exercise and building community cohesion, thereby maintaining the mental health of residents.